Museu de Ciências Morfológicas: um lugar diferente na Universidade Federal de Minas Gerais The Museum of Morphological Sciences: a different place at the Universidade Federal de Minas Gerais - Maria das Graças Ribeiro (História, Ciências, Saúde: Manguinhos)
Este trabalho mostra um novo museu de ciências, cujo trabalho junto ao público é um convite enfático ao conhecimento da estrutura e funcionamento do organismo humano, como forma de entender a vida, para preservá-la com qualidade. The article introduces a new science museum, one that works actively to engage its audience in learning about the structure and functioning of the human organism, so that it can understand life and thus protect its quality.